Morphological features of the lateral plantar ligament of the transverse metatarsal arch. Issue 7 (9th October 2020) - Edama, Mutsuaki; Takabayashi, Tomoya; Hirabayashi, Ryo; Yokota, Hirotake; Sekine, Chie; Inai, Takuma; Matsuzawa, Kanta; Otsuki, Tomofumi; Maruyama, Sae; Kageyama, Ikuo
Abstract: The aim of this study was to elucidate the morphological characteristics of the lateral Lisfranc ligament in a large sample. This investigation examined 100 legs from 50 cadavers. Each of the lower limbs was dissected to identify the plantar aspect of the transverse metatarsal arch, and morphological characteristics of the lateral plantar ligament were assessed, including the length, width, and thickness of the fiber bundles. The majority of plantar ligaments originated from the base of M5 and the plantar aspect of the lateral cuneiform (LC). The lateral plantar ligament could be classified into three types: Type I, a band‐like fiber bundle originating from the base of M5 to the LC (41%); Type II, originating from the base of M5 and the plantar aspect of LC and mostly connected the blending the fiber bundles of the tibialis posterior (TP) and long plantar ligament (LPL) (21%); and Type III, with no ligaments originating from the base of M5 and plantar aspect of the LC (38%). The morphological characteristics of Type I lateral plantar ligament were as follows: length, 31.8 ± 3.7 mm; width, 2.3 ± 1.0 mm; and thickness, 0.2 ± 0.3 mm. The morphology of the lateral plantar ligament showed variation, originating from the base of M5 and the plantar aspect of LC most commonly, but this was not the case in 38% of limbs. The findings suggest that the lateral plantar ligament might play a role in the transverse tarsal arch, indicating a cooperative mechanism with the TP and LPL.